Sequential combination of nanofiltration and ettringite precipitation for managing sulfate-rich brines - Jin, Yongxun; Lee, Jiho; Gwak, Gimun; Chung, Chong Min; Choi, Jae Woo; Cho, Kangwoo; Hong, Seok Won (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
The sequential combination of nanofiltration (NF) and ettringite precipitation to manage sulfate-rich brine is proposed. In this study, NF experiments clearly demonstrated that sulfate-containing wastewater was effectively concentrated by the NF process (concentrate factor, CF > 5) with insignificant membrane fouling. Ettringite precipitation was implemented as an alternative to lime precipitation to process sulfate-rich brine resulting from the NF operation. More than 93% of the sulfate ions were removed by ettringite precipitation, whereas lime precipitation removed less than 28% under the same conditions due to the difference in their solubility. However, with highly concentrated NF brine (CF > 5), the pH and sulfate concentration of the supernatant were higher than the discharge limit. Therefore, optional blending of the supernatant after ettringite precipitation with the NF permeate was proposed to satisfy the discharge limit for sulfate. The sequential operation consisting of NF and ettringite precipitation enables sulfate-rich wastewater to be treated effectively, minimizing its negative impact by reducing the brine volume and enabling the water to be reused.